2007
DOI: 10.1063/1.2432915
|View full text |Cite
|
Sign up to set email alerts
|

Rotating multipoles on the f- and γ-planes

Abstract: A family of semianalytical solutions is presented describing multipolar vortical structures with zero total circulation in a variety of two-dimensional models. Analytics are used to determine the form of a multipole edge, or separatrix, and the solution outside this separatrix. The interior is solved using a Newton-Kantorovich (successive linearization) procedure combined with a collocation method. The models considered are the quasigeostrophic f- and γ-planes, with either the rigid-lid or free-surface conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
24
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 43 publications
6
24
0
Order By: Relevance
“…6, 8-10 and the references therein). In conformity with the experiments, our most recent numerical results (that will be published elsewhere) indicate that the tripole, quadrupole, and higher semi-analytical multipolar solutions with zero total circulation [8][9][10] are stable, feebly stable, and unstable, respectively. For all that, in studying the stability of coherent vortical structures, any progress achieved analytically (even if owing to serious simplifications) is always appreciated.…”
Section: Introductionsupporting
confidence: 81%
“…6, 8-10 and the references therein). In conformity with the experiments, our most recent numerical results (that will be published elsewhere) indicate that the tripole, quadrupole, and higher semi-analytical multipolar solutions with zero total circulation [8][9][10] are stable, feebly stable, and unstable, respectively. For all that, in studying the stability of coherent vortical structures, any progress achieved analytically (even if owing to serious simplifications) is always appreciated.…”
Section: Introductionsupporting
confidence: 81%
“…It was shown that these semianalytical solutions reproduce the main features of experimental tripoles 13,14 and numerical quadrupoles 29 concerning their shape, flow pattern, and the form of the vorticitystreamfunction relationship. This work was later extended by Kizner et al 30 in order to construct semianalytical solutions for multipolar vortices with more satellite vortices and to incorporate the quasigeostrophic equivalent-barotropic ͑1 1 2 -layer͒ and ␥-plane approximations.…”
Section: Introductionmentioning
confidence: 99%
“…Also, evidence of the onset of hexapolar and heptapolar vortices was found. The experimentally produced multipoles will be compared with the semianalytical solutions for multipolar vortices obtained by Kizner et al, 30 with the emphasis put on the form of the vorticity versus streamfunction relation and the crosssectional distribution of vorticity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 More recently, numerical and laboratory experiments [17][18][19][20][21][22][23][24][25][26] indicate the existence of coherent rotating tripolar vortex structures, and higher connectivity analogs have also been found numerically. 27,28 Further analytical studies of the vortex equilibrium problem can be found in other studies.…”
Section: Introductionmentioning
confidence: 99%